59.5k views
4 votes
Let f(x) = -2x - 7 and g(x) = -4x + 6. Find (gof)(-5).

User Max Tromp
by
4.7k points

2 Answers

5 votes

Answer:


(gof)(-5)=-6

Explanation:

One is given the following information;


f(x)=-2x-7\\g(x)=-4x+6

One is asked to find the following,


(g o f)(-5)

The expression (
gof) is another way to denote (
g(f(x))), in essence, substitute function (f) into function (g) in place of parameter (x). The simplify to find the resulting function;


g(f(x))\\=-4(-2x-7)+6\\=(-4)(-2x)+(-4)(-7)+6\\=8x+28+6\\=8x+34

One is asked to evaluate the function (
gof) for (-5). Substitute (-5) into the function and simplify to evaluate;


(gof)(-5)=8x+34\\=8(-5)+34\\=-40+34\\=-6

User Frank Krueger
by
5.3k points
6 votes

Answer:

(g ○ f )(- 5) = - 6

Explanation:

Evaluate f(- 5), then substitute the value obtained into g(x)

f(- 5) = - 2(- 5) - 7 = 10 - 7 = 3 , then

g(3) = - 4(3) + 6 = - 12 + 6 = - 6

User David Rearte
by
4.9k points